Competency-Based Teaching Method and Its Relationship to Physical Self-Description among High School Students - lazreg, ahmed (sports creativity, 2025)
Physical education is considered an accredited academic subject with educational and instructional objectives. It holds an important place in the Algerian educational system and cannot be dispensed with at any stage due to its role in developing social, physical, and psychological aspects, such as forming an overall self-image, leading to the development of one's physical self. The latter can only be understood or recognized through physical and sports activities. Educational institutions have recently shown great interest in teaching this core subject because of its significant importance to students, especially during adolescence. This is due to its role in promoting positive development in psychological aspects, through which the student finds themselves capable of assessing their abilities and skills in performing various movements and sports skills in different physical activities during physical education classes. They also achieve a certain level of emotional adaptation and stability in various situations they encounter. Understanding With others and in the tasks they perform, it also plays an important role in achieving athletic accomplishment. As for an individual with a negative self-concept, they are characterized by a lack of confidence in their abilities; the weaker the individual's self-acceptance, the weaker their psychological adjustment, making it difficult for them to overcome problems and challenges they face, and exposing them to situations of psychological conflict that affect their behavior and performance level. In light of the above, the researcher in this study emphasizes the necessity of strengthening the physical self-concept of high school students through continuous assessment of the students' level of perception and conducting physical fitness tests to enhance their self-awareness. Although physical and sports activity is considered one of the most important activities and curricula in which we find numerous abilities and situations addressed and developed due to its fundamental components (psychological – motor – social – skill – physical), there is still a need for an evaluative study of what exists in the field in order to identify weaknesses for remediation and uncover strengths to reinforce them. On this basis, the main question arises as follows: Does the competency-based teaching method have a related impact? The Communicative Aspect of Body Image Among High School Students